Serum Neurofilament Light Chain as a Discriminatory Biomarker and Predictor of Disease Trajectory in Amyotrophic Lateral Sclerosis: A Systematic Review and Meta-Analysis - Cindy Permata Sari; I Ketut Sumada; Desie Yuliani; Ni Made Kurnia Dwi Jayanthi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Amyotrophic lateral sclerosis is a rapidly progressive, fatal neurodegenerative disorder characterized by the deterioration of upper and lower motor neurons. Diagnostic delays are frequently caused by phenotypic overlap with various mimic disorders. Serum neurofilament light chain has emerged as a promising biomarker; however, its precise discriminatory capacity against mimics and its utility in predicting disease trajectory necessitate rigorous quantitative evaluation. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic search of MEDLINE/PubMed, Embase, Cochrane Central, and Scopus was conducted. Eight high-quality primary research articles met the strict inclusion criteria for data extraction. Studies evaluating diagnostic utility (amyotrophic lateral sclerosis versus mimic disorders) and prognostic value (survival hazard ratios) were included. Random-effects models calculated pooled standardized mean differences for diagnostic accuracy and pooled hazard ratios for overall survival. Results: The meta-analysis analyzed data from 8 cohorts. Serum neurofilament light chain levels were significantly elevated in amyotrophic lateral sclerosis patients compared to mimic disorders, yielding a pooled standardized mean difference of 1.43 (95% confidence interval: 1.15 to 1.71, p < 0.001). High heterogeneity was observed (I-squared = 82%). For prognostic evaluation, a pilot quantitative synthesis of two cohorts demonstrated that higher baseline concentrations correlated with increased mortality risk, showing a pooled hazard ratio of 1.95 (95% confidence interval: 1.58 to 2.41, p < 0.001). Conclusion: Serum neurofilament light chain is a robust discriminatory biomarker capable of distinguishing amyotrophic lateral sclerosis from confounding mimic disorders. Furthermore, baseline concentrations offer prognostic value for survival outcomes. These findings support the cautious integration of this biomarker into clinical algorithms, though broader multi-center prognostic studies are required.